Parental resilience or dyadic resilience as heal th promoting variable: an overview in scientific production - Veiga-Branco, Augusta (2017)
Although studies on resilience have increased in recent years, there is scarce evidence of family resilience with children with special needs. The present study starts in the recognition of the symbiosis effect between the concepts of Positive Psychology (Seligman, 2000), Family Resilience and Emotional Education (Bisquerra, 2000; Veiga Branco 2004, 2005, 2007), to achieve the objective of enabling families to promote positive feelings. The aim of this research is to present an overview review about family resilience within families of a child with special needs and its forms of promotion in terms of health promotion in general and psycho-social disturbance in particular, during every professional contact within this families. This research overviews national and international scientific production in the area of family resilience by analyzing abstracts published between 2011 and 2016 according to the following criteria: research topics, sample size, instruments/techniques used for data collection. The databases PsycInfo, SpringerLink and Wiley Online Library were searched. Recognizing caring a child with special needs as an adversity and source of additional stress to families, resilience emerges as a fundamental element of helping families. The results suggest the need to expand the studies on family resilience. It is also evident that professionals need to be aware not only of the risk factors but also of the protective ones when promoting family resilience. It must be recognized the need to train parents and professionals in emotional education.